2016
DOI: 10.1039/c5sc03363b
|View full text |Cite
|
Sign up to set email alerts
|

A dual-functional lanthanide nanoprobe for both living cell imaging and ICP-MS quantification of active protease

Abstract: A novel nanoprobe is successfully developed for simultaneous living cell imaging and sensitive quantification of caspase-3 in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Some works have been published about the bimodal detection concept using fluorescence and ICP-MS [8,[27][28][29]. Bustos et al [8] reported a comparison of both detection modes with CdSe/ZnS QDs through the measurement of Cd in the case of ICP-MS. Other examples include the use of a nanoprobe composed of europium chelated by 1,10-bis(50-chlorosulfo-thiophene-20-yl)-4,4,5,5,6,6,7,7-octafluorodecane-1,3,8,10-tetraone [28], the synthesis of hybrid labels containing both a DTPA chelate (coordinated with either 165 Ho or 111 In) and a Cy5 fluorescent dye [27], or by combining a fluorescent dye (Cy3) with upconversion NPs [29]. Those probes are compose either of just one metal atom or of atoms of different heteroatoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some works have been published about the bimodal detection concept using fluorescence and ICP-MS [8,[27][28][29]. Bustos et al [8] reported a comparison of both detection modes with CdSe/ZnS QDs through the measurement of Cd in the case of ICP-MS. Other examples include the use of a nanoprobe composed of europium chelated by 1,10-bis(50-chlorosulfo-thiophene-20-yl)-4,4,5,5,6,6,7,7-octafluorodecane-1,3,8,10-tetraone [28], the synthesis of hybrid labels containing both a DTPA chelate (coordinated with either 165 Ho or 111 In) and a Cy5 fluorescent dye [27], or by combining a fluorescent dye (Cy3) with upconversion NPs [29]. Those probes are compose either of just one metal atom or of atoms of different heteroatoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This LOD might be improved using a lanthanidecontaining optical and mass signals affordable molecule, for example, Eu-BCTOT for fluorescent imaging and ICPMS quantification because of the luminescent property of the Eucomplex. 35 The dynamic range of the Sias number against 10 B ICPMS intensity was from 10 −13 to 10 −8 mol Sia (R = 0.9990, RSD = 5.5% at 10 −9 level, n = 5) (Figure 3c).…”
mentioning
confidence: 96%
“…In total, 1.41 × 10 11 Sias (2.35 × 10 –13 mol) per SMMC-7721cell (RSD = 5.9%, n = 5) and 4.71 × 10 8 Sias (7.81 × 10 –16 mol) per LO2 cell (RSD = 6.0%, n = 5) were quantified with 0.24 pmol LOD (3σ) of B-tagged Sias, which were well in agreement with those using DBCO-DOTA-Eu, although the LOD (3σ) was almost 27-times higher. This LOD might be improved using a lanthanide-containing optical and mass signals affordable molecule, for example, Eu-BCTOT for fluorescent imaging and ICPMS quantification because of the luminescent property of the Eu-complex . The dynamic range of the Sias number against 10 B ICPMS intensity was from 10 –13 to 10 –8 mol Sia ( R = 0.9990, RSD = 5.5% at 10 –9 level, n = 5) (Figure c).…”
mentioning
confidence: 99%
“…Besides outstanding luminescent properties, the state-of-the-art fluorescent materials, involving metal–organic frameworks, quantum dots, noble metal nanoclusters, and upconversion lanthanides nanoparticles, often intrinsically contain a great number of metal stable isotopes. , The metal stable isotopes can be efficiently quantified by ICPMS. Consequently, bimodal detection is potentially available by utilizing both fluorescence spectrometry and mass spectrometry, which would integrate the advantages of the two analytical techniques and may promote our understanding on explosive monitoring processes.…”
mentioning
confidence: 99%
“…18,19 The metal stable isotopes can be efficiently quantified by ICPMS. Consequently, bimodal detection is potentially available by utilizing both fluorescence spectrometry and mass spectrometry, 20 which would integrate the advantages of the two analytical techniques and may promote our understanding on explosive monitoring processes. Herein, we report the design and construction of a bimodal methodology for both sensitive in-field fluorescence detection and accurate laboratory mass spectrometric quantification of explosives by taking advantage of the characteristic fluorescence and ICPMS response of copper nanoparticles (CuNPs).…”
mentioning
confidence: 99%